2010
DOI: 10.1002/ca.21000
|View full text |Cite
|
Sign up to set email alerts
|

Termination of the vertebral veins: Evaluation by multidetector row computed tomography

Abstract: The purpose of this study was to evaluate the topographic anatomy of the vertebral vein (VV) in the lower neck and thoracic inlet using CT scans. Enhanced CT scans using 32-MDCT were obtained for 199 consecutive patients. Reconstructed images with 1-mm section thickness/intervals were evaluated by two radiologists examining the drainage point, number, and route of VVs using frame forwarding and the rewind function on the DICOM viewer. The VV was classified into four types as follows: Type A (80.6%), a VV that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The vertebral vein passes through the transverse foramina from the atlas to the 6th cervical vertebra [ 3 , 4 ]. After exiting the transverse foramen of the 6th vertebra, it subsequently subsequently runs anterolateral to the vertebral artery and posterior to the IJV and drains the innominate vein [ 3 , 4 ]. In this case, ultrasound revealed that the location of the inserted catheter was posterior to the IJV ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The vertebral vein passes through the transverse foramina from the atlas to the 6th cervical vertebra [ 3 , 4 ]. After exiting the transverse foramen of the 6th vertebra, it subsequently subsequently runs anterolateral to the vertebral artery and posterior to the IJV and drains the innominate vein [ 3 , 4 ]. In this case, ultrasound revealed that the location of the inserted catheter was posterior to the IJV ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The DTF has been studied in relation to the VA because the V2 segment of the VA passes through the transverse foramen (TF) from C6 to C2 (Jovanovic, ). Therefore, the TF has obvious clinical implications in cases of possible compression of or trauma to structures that cross it, especially in relation to the VA, the sympathetic nerves that innervate the VA, and the vertebral vein (VV) (Taitz et al, ; Miyake et al, ).…”
Section: Introductionmentioning
confidence: 99%